Material estructurado y el pensamiento lógico- matemático en los niños de 4 a 5 años de la Unidad Educativa Fiscomisional Manuel José Rodríguez de la parroquia Malacatos, periodo 2022-2023 - Pérez Maza, Stefany Nathaly (2024)
The development of logical-mathematical thinking is of paramount importance as it enables the engagement of basic skills and abilities. Once these competencies as acquired, individuals can solve mathematical problems in an appropriate and straightforward manner as well as coexist within their own environment. Therefore, this research aimed to determine how structured materials enhance logical-mathematical thinking in children aged 4 to 5 years at Manuel José Rodriguez primary school in the Malacatos parish during the 2022-2023 school period. A mixed approach was employed, encompassing both qualitative and quantitative results. The inductive-deductive method was used to analyze and establish the problematization, providing a meaningful framework for the research’s outcomes. Additionally, the analytic-synthetic method was used to collect information regarding the two variables. The results obtained through the EVAMAT-0 battery, administered to twenty-five children, revealed difficulties in mathematical skills during the pre-test, including challenges with numerical sequences, object classification by size, understanding of concepts, recognition of both primary and secondary colors and number-quantity relationships, among others. These difficulties placed them in the 87% lower zone. However, after the intervention, there was a reduction in the percentage to 12%, indicating significant improvements. In conclusion, structured materials strengthen mathematical learning by enabling hands-on manipulation of resources, facilitating the acquisition of new knowledge and basic skills. This approach effectively reinforces learning for critical thinking. Keywords: skills, basic skills, difficulties, didactic, manipulation, resources.